HARDWARE-SOFTWARE MATH LIBRARY FOR SOPC - Zinchenko, U. E.; Gritsenko, А. А.; Zeleneva, I. Y.; Voitov, G. V. (Radio Electronics, Computer Science, Control, 2011)
The authors propose a method of creation of a math library for SoPC and a set of the required tools. Using this library, it is possible to vary the SoPC structure according to the user’s requirements and available hardware resources.